2011
DOI: 10.17221/169/2010-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of seven candidate genes with performance traits in Czech Large White pigs

Abstract: AbstrACt:In this study association analyses were performed between genes tagged SNP (IGF2, NAMPT, DGAT1, MYF4, MC3R, MC4R and MYOD1), performance traits (backfat thickness, lean meat content, average daily gain from birth to the end of the test, average daily gain in test) and estimated breeding values (EBVs) in a population of Czech Large White sows (n = 101). Genotyping of all SNPs was performed by SNapShot with the exception of SNP within NAMPT gene for which HpaII PCR-RFLP assay was used. The following si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the other hand, an interaction among and within loci may also be shown in the ranking of chromosomes. Complex genetic determination of meatness has been reported by a number of authors (Kamiński et al, 2009;Srikanchai et al, 2010;Weisz et al, 2011;Fontanesi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, an interaction among and within loci may also be shown in the ranking of chromosomes. Complex genetic determination of meatness has been reported by a number of authors (Kamiński et al, 2009;Srikanchai et al, 2010;Weisz et al, 2011;Fontanesi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although these three mutations do not change amino acid sequences, synonymous SNPs can affect in vivo protein folding, mRNA stability (Duan et al, 2003), and Values with different superscript letters (a, b) within the same line differ significantly at P < 0.05. splicing (Pagani et al, 2005), and consequently affect function as well as gene expression and phenotype Sauna et al, 2007). Synonymous mutations in MC3R are closely associated with daily weight gain, body weight, and feed efficiency in pigs and red foxes (Skorczyk et al, 2011;Weisz et al, 2011); further studies are required in order to investigate how SNPs affect variations in these traits. BMTs and MQTs are quantitative traits controlled by multiple genes (Boukha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, over 20 mutations in MC3R have been identified (Cieslak et al, 2013), and 6Thr>Val, 81Val>Ile, and 335Ile>Ser are strongly predisposing to obesity (Tao, 2007). In the porcine MC3R, two silent single-nucleotide polymorphisms (SNPs) have been detected, and are significantly related to daily weight gain (Weisz et al, 2011). Furthermore, extensive studies on the MC3R gene in the chicken, dog, red fox, and Chinese raccoon dog have revealed variable levels of polymorphism (Sharma et al, 2008;Skorczyk et al, 2011), and association studies conducted on chickens and red foxes have revealed significant relationships with body weight, carcass weight, feed efficiency, and abdominal fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…The high efficiency of pig breeding is absolutely necessary for competitiveness under today's difficult economic conditions (Weisz et al, 2011). One of goals of animal genetics is to locate and identify loci that are responsible for economical important traits such as meat performance, reproduction, and product qualities which are the most significant factors for pork production efficiency (Bulla et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The myogenin is a transcription factor specific to skeletal muscle and fulfils a key function in muscle differentiation by controlling the onset of myoblast fusion and the establishment of myofibres. Genetic variation in the MYF4 gene can be associated with differences in myoblast and myofibril numbers (Weisz et al, 2011). Ernst et al (1993) and Soumillion et al (1997) detected using endonuclease MspI gene three polymorphic sites in the MYF4, in the promoter region, the second intron and the 3' side of the gene.…”
Section: Introductionmentioning
confidence: 99%